Management of Polyneuromyopathy in a Critically Ill Patient with a Left Ventricular Assist Device - Gjerakaroska Savevska, Cvetanka; Gjerakaroska Radovikj, Marija; Daniela Gechevska; Koevska, Valentina; Mitrevska, Biljana; Gocevska, Marija; Matjanoska, Lidija Stojanoska; Kalchovska Ivanovska, Biljana; Manoleva, Maja (Macedonian Academy of Sciences and Arts, 2022)
Critical illness polyneuromyopathy after cardiac surgery is often unrecognized and is a rarely reported clinical condition. It is characterized by more proximal than distal symmetrical flaccid muscle weakness and difficulty in weaning from a respirator. When done in a timely manner, rehabilitation prevents early complications and reduces the length of hospitalization. Rehabilitation leads to better motor outcome, improves short-term and long-term functionality, and results in a better quality of life.
Keywords: critical illness; polyneuromyopathy; rehabilitation; LVAD